Microclimate effects and influential mechanisms of four urban tree species underneath the canopy in hot and humid areas - Feng, Xianhui; Wen, Huan; He, Mu; Xiao, Yiqiang (Frontiers in Environmental Science, 2023)
Purpose: Urban trees play a key role in ameliorating extreme urban climates in cities. At the micro-level, it is crucial to investigate the variations in microclimates affected by the canopies of different tree species. The significance of this research is to provide scientific evidence for the selection of tree species in urban planning that can improve the local microclimate. This study examines the factors of microclimate (air temperature, relative humidity, wind environment, and solar radiation) underneath the canopy of four different evergreen tree species in hot and humid areas. Furthermore, the correlation between the physiological characteristics of these tree species and microclimate was statistically analyzed using data on the physiological parameters of the trees and microclimate factors. Methods: In this study, four tree species were selected for field measurements: Ficus microcarpa L. f., Ficus virens Aiton, Bauhinia x blakeana Dunn, and Cinnamomum camphora (L.) Presl. We used the HOBE (H21-0024, onset) to measure three climatic parameters (Temperature, Relative Humidity, and Instantaneous Wind Speed), and the Li-6400 Portable Photosynthesis System to measure five plant physiological parameters: Stomatal Conductance (Gs), Leaf Temperature (Tleaf), Leaf Surface Relative Humidity (RHsfc), Photosynthetically Active Radiation (PAR), and Leaf-level Vapor Pressure Deficit (Vpdl). The observations were conducted during winter (January 16 - January 22) and summer (August 7 - August 22). The investigation periods were 9:00–11:00, 12:00–14:00, and 16:00–18:00, and data were recorded at 15-min intervals. The observational data obtained were analyzed using statistical methods, including one-way analysis of variance, Pearson correlation coefficient, and multiple regression analysis. Results: The results of this study indicated that the four tree species being measured had different effects on the microclimate at the sites in both the winter and summer seasons. During the 7-day observation in the summer, the cooling effect of the four tree species was significant. The relative humidity underneath the canopies was 3%–11% higher than that of weather stations. The instantaneous wind speed in the afternoon was relatively higher than at other times. The solar radiation intensity was dramatically reduced by 85%–95%. During the 7-day observation in the winter, the trees had a warming effect in the morning. The relative humidity underneath the canopies was 10%–20% higher than that of the weather stations. The areas underneath the canopies were windless in the afternoon. The solar radiation intensity was reduced by 78%–95%. Ficus microcarpa was found to be one of the most effective tree species for increasing the relative humidity and reducing solar radiation intensity in hot and humid areas. Additionally, the highest instantaneous wind speed was observed in the areas underneath the canopies of F. virens and C. camphora. Statistical tests revealed that the air temperature and the instantaneous wind were extremely significantly correlated with Tleaf and RHsfc. Conclusion: The four urban tree species studied had varying degrees of effect on air temperature, relative humidity, wind speed, and reducing solar radiation intensity in the areas underneath their canopies. Furthermore, these trees demonstrated varying abilities to improve microclimate conditions in different seasons. The four trees had a cooling effect in the summer. The instantaneous wind speed was calm in the afternoons during the winter in contrast to being relatively high speed in the afternoons during the summer. This characteristic is beneficial to warmth in winter and coolness in summer. In terms of the internal influence mechanisms, the results of the analysis indicated that microclimate factors were significantly correlated with the physiological parameters of the trees. Tleaf, RHsfc, and Vpdl were significant physiological parameters and had different contribution rates to microclimate factors.